187k views
5 votes
The expression -3m - [2m + (5 - m)] + 7 was simplified as 2 - 4m. Without simplifying, explain how you can show that it has been simplified correctly.

User Tomfl
by
5.3k points

1 Answer

2 votes

Answer: It is correctly simplified form.

Explanation:

Since we have given that


-3m-[2x+(5-m)]+7

We need to simplify the above expression:


-3m-2m-5+m+7\\\\=-5m+m+2(\text{gather the like terms})\\\\=-4m+2\\\\=2-4m

So,
-3m-[2x+(5-m)]+7=2-4m

Hence, it is correctly simplified form.

User Partack
by
5.1k points